(untitled) (Orinoquia, 2019)
Several bat species are able to use environments highly modified by humans, and in Colombia, little is known about the natural history of urban bats. Consequently, we studied the buildings used by bats as roosts in a university campus in the foothills of the Eastern Cordillera in Villavicencio, Meta. We measured for each roosting site: height to the perching site, tree cover, and distance to light poles. We identified 13 buildings with 15 roosting sites; seven were used by Saccopteryx leptura (Lesser Sac-winged Bat), four by Carollia perspicillata (Seba’s Short-tailed Bat), three by Molossus molossus (Pallas’s Mastiff Bat), and two by Phyllostomus elongatus (Lesser Spear-nosed Bat). Molossus molossus and C. perspicillata shared one roosting site. Height to the perching site, canopy cover, and distance to light poles were highly variable. The roosts were between 1.83-13.5 m, whereas tree cover and distances to light poles were between 22.75-87.5%, and 3.5-39.92 m, respectively. The number of individuals within the roosts of S. leptura was positively correlated to the distance to the nearest pole and the height of the perch site. Thus, these characteristics of the artificial roosting sites appear to be related to site quality for this bat species. We suggest avoiding roosts in work places close to people to reduce conflicts between bats and humans on campus, due to the likelihood of disease transmission. We also suggest evaluating the use of artificial roosting sites, such as bat boxes, as alternatives to buildings to maintain the ecosystem services provided by these mammals on campus.